2009
DOI: 10.3844/ajassp.2009.1669.1674
|View full text |Cite
|
Sign up to set email alerts
|

Wave V Detection Using Instantaneous Energy of Auditory Brainstem Response Signal

Abstract: Problem statement: ABR machine is a well known machine that has been used on detection of hearing problem especially for babies or children. In ABR, wave V is the most prominent and robust wave that has been used as indicator of hearing loss. However, a fast detection of the wave V is necessary in order to implement newborn hearing screening. There are various types of signal processing methods introduced by researchers in order to achieve the target. Fast Fourier Transform (FFT) and wavelet transform are well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The physiological changes is an effect of the increased testosteroneoestrogen ratio at that period. A similar decreasing of F0 can be caused by the habit of smoking (Gilbert and Weismer, 1974;Rushaidin et al, 2009). For male speech, the dramatic decrease in F0 during puberty duration has been observed to continue with subsequent deceleration until about 35 years of age.…”
Section: Fundamental Frequency Contour (F0 Contour)mentioning
confidence: 82%
“…The physiological changes is an effect of the increased testosteroneoestrogen ratio at that period. A similar decreasing of F0 can be caused by the habit of smoking (Gilbert and Weismer, 1974;Rushaidin et al, 2009). For male speech, the dramatic decrease in F0 during puberty duration has been observed to continue with subsequent deceleration until about 35 years of age.…”
Section: Fundamental Frequency Contour (F0 Contour)mentioning
confidence: 82%
“…In [7], the authors used the estimation of first and second derivatives of the signals, but only for high intensity level (90 dB). Also, in [4] the instantaneous energy method was introduced for wave V detection at high stimulation intensities (80 dB). Our results showed that this statistical procedure can be used also at low stimulation intensities.…”
Section: Designed Algorithmmentioning
confidence: 99%
“…In order to optimize the diagnosis and speed up this procedure, several methods have been proposed for automatic ABR (aABR) detection [4][5][6][7][8]. The most widely used is to compare the recorded tracings with a template that represents expected results.…”
Section: Introductionmentioning
confidence: 99%
“…Each type of the noises is recorded separately and its amplitude is scaled to acquire the desired level of noise. In other words, the energy of noise and the speech signal are calculated then these signals are merged with five levels of SNRs of 0, 5, 10, 15 and 20 dB (Shareha et al, 2009;Geravanchizadeh and Rezaii, 2009;Rushaidin et al, 2009;Rajarathinam and Parmar, 2011).…”
Section: Fundamental Frequency Contour (F0 Contour)mentioning
confidence: 99%